Determinants of Loan Performance in P2P Lending - Möllenkamp, Nilas (Student Undergraduate Research E-journal!, 2017)
This research paper investigates the influential factors of loan performance in the online P2P lending industry. The study analysed 143,654 P2P loans that were funded on the P2P lending platform Lending Club between 2012 and 2013 and found evidence that the assigned credit grade of loans is the most influential factor on loan success and default. Furthermore, loan amount and annual income are significant predictors. The variables debt-toincome ratio, inquires in the last 6 months, open credit lines and revolving credit balance were only found significant for some credit grade classes.